2022
DOI: 10.1007/s11135-022-01350-8
|View full text |Cite
|
Sign up to set email alerts
|

Measuring partisan polarization with partisan differences in satisfaction with the government: the introduction of a new comparative approach

Abstract: In recent years, the attention of political scientists investigating political polarization has turned from the ideological aspects of polarization to its partisan and affective aspects. This recent turn implied that this area has experienced an urgent need to create appropriate polarization indices that are backed with high-quality data across time and countries to carry out comparative research. This paper argues that existing polarization indices mostly fail to adequately include the most important aspect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 39 publications
(69 reference statements)
0
12
0
Order By: Relevance
“…Our results prove this to be the case. It is worth highlighting that partisan polarisation existed in Poland before the COVID-19 pandemic, as confirmed by the results of the European Social Survey (2002–2020), where Poland was described as a highly polarised country along with Spain, Greece, Turkey, Croatia and Hungary [ 76 ].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Our results prove this to be the case. It is worth highlighting that partisan polarisation existed in Poland before the COVID-19 pandemic, as confirmed by the results of the European Social Survey (2002–2020), where Poland was described as a highly polarised country along with Spain, Greece, Turkey, Croatia and Hungary [ 76 ].…”
Section: Discussionmentioning
confidence: 96%
“…In the analysis of their impact on vaccine behaviours and attitudes, political preferences were considered through their binary distribution (supporting the ruling coalition vs. not supporting the ruling coalition). This approach refers to partisan polarisation defined as a tendency to perceive the ‘political life of a community (…) as a battle between two partisan sides’ [ 76 ] (p. 2). Electoral preferences alone (voting for one party or the other) do not necessarily translate into strong partisan polarisation; however, the fact that certain phenomena (e.g., related to the pandemic) are perceived through the prism of ideological affiliations may be indicative of this form of attitude divergence.…”
Section: Discussionmentioning
confidence: 99%
“…It was found in several studies that American conservatives and liberals endorse different moral foundations to a different extent. The American liberal-conservative division in European context is often substituted with left-right division, however in a non-bipolar system partisan differences cannot always be explained by this distinction (Patkós 2023). For instance, Kivikangas et al (2017) empirically found that in the Finnish political landscape"liberalism-conservatism"cannot interchangeably used with"left-right"in terms of political spectrum division.…”
Section: Descriptive Analysismentioning
confidence: 99%
“…the liberalism-conservatism division can be substituted with left-right in the European context (Kivikangas et al 2017;Patkós 2023). This can be the result of general political discourse: politicians' topics potentially have a general level of similarity to the MFD 2.0 lexicon.…”
Section: Descriptive Analysismentioning
confidence: 99%
“… Ertan et al ( 2023 ) Highlights the issue of political polarization during extreme events and its negative impact on response and recovery operations. Patkós ( 2023 ) Highlights the need for a relook at polarization indices in light of an attention shift from ideological aspects to partisan and affective aspects and introduces a partisan polarization index, and compares it with other indices. Political disinformation Levendusky ( 2013 ) Highlights the role of partisan media outlets and slanted news presentations in leading viewers to develop more negative perceptions and lower trust for other parties alongside lower support for bipartisanship.…”
Section: Appendix a List Of Countries For Both Main And Supplemental ...mentioning
confidence: 99%